ANALISIS SISTEM PENDAFTARAN RAWAT JALAN DI PUSKESMAS SIDAMULYA KABUPATEN CIREBON - Dini Sekarlati; Sri Nurcahyati; Hendri Rosmawan (Jurnal Kesehatan Mahardika, 2019)
Health information system is part of national health system consisted by data, human and process and combination of hardware, software, information and technology. Health information systems supported individual and community services such as administrative services with the registration process on health services. The existing registration system still experienced by some obstacles such as systems that have not been integrated and overlapping in data collection. The purpose of this study is to analyze the enrollment registration system in Sidamulya Public Health Center ranging from input, process to output. The design of this research used a qualitative type with study case approach. The sample in this research is 3 registration officer. Technique of taking data used interviews and observation. Registration system currently used the manual and electronic systems. Manual registration used register book while the electronic registration system has been supported SIKDA Generic 1.4 and P-care applications. Data obtained from registration will be captured and processed using Ms. Excel. From these treatments resulted reports on outpatient visits reported. To improved service better by made SIKDA Generik 1.4 evaluation and registration officer training.